Seminal Plasma ExLncRNA Pairs: Updating Perspectives in the Search for Testicular Spermatozoa Retrieval Biomarkers in Nonobstructive Azoospermia Patients with mTESE by WGCNA - Cao, Haiming; Wang, Chuntao; Cai, Ruilin; Wan, Zi; Ma, Lin (Urology Journal, 2023)
Purpose: This study aims to find candidates for testicular spermatozoa retrieval biomarkers among the seminal plasma exLncRNA pairs. Materials and Methods: A set of exLncRNA pairs with the best potential biomarkers was selected and validated in 96 NOA samples. Weighted correlation network analysis (WGCNA) and Least Absolute Shrinkage and Selection Operator were used to identify possible biomarkers for these pairs (LASSO). These pairs' potential biomarkers were identified using receiver operating curves. Confusion matrices and sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), FP, false-negative rates (FNR), and F1 scores are calculated. Through F1 scores, we selected the best threshold value. Results: The relative differential expression of each pair in testicular spermatozoa retrieval (+) and testicular spermatozoa retrieval (-) men were validated. The six pairs displayed the best biomarker potential. Among them, CCDC37.DT-LOCI00505685 pair and LOC440934- LOCI01929088 (XR_001745218.1) pair showed the most significant potential and stability for detecting testicular spermatozoa retrieval in the selected and validated cohort. Conclusion: CCDC37.DT-LOCI00505685 pair and LOC440934- LOCI01929088 (XR_001745218.1) pair have the potential to become new molecular biomarkers that could help to select clinical strategies for microdissection testicular sperm extraction.